Effects of acceptance and commitment therapy on negative emotions, automatic thoughts and psychological flexibility for depression and its acceptability: a meta-analysis - Yanxiang Zou; Ruxuan Wang; Xiaochen Xiong; Cheng Bian; Shirui Yan; Yanhong Zhang (BMC Psychiatry)
Abstract Background Acceptance and Commitment therapy (ACT) has been widely used in patients with depression. However, its effectiveness in improving psychological flexibility and reducing automatic thoughts remains uncertain. This meta-analysis of randomized controlled trials (RCTs) aimed to evaluate the effects of ACT on depression, anxiety, automatic thought, and psychological flexibility in patients with depression, as well as its acceptability. Methods RCTs were systematically searched in nine databases and gray literature, with the last update on March 25, 2025. Effect sizes were synthesized using a random-effects model, and subgroup analyses were conducted to explore potential heterogeneity. Publication bias was corrected using three methods: PET-PEESE, selection models, and robust Bayesian meta-analysis. The certainty of evidence was evaluated using the GRADE approach. Results A total of 13 RCTs from 1362 patients were included in this meta-analysis. Pooled results showed that ACT significantly improved depression [SMD = − 0.66 (− 0.80, − 0.52), P <.001, I2 = 24% (0%, 75%), Certainty: Low], anxiety [SMD = − 0.43 (− 0.77, − 0.10), P <.05, I2 = 77% (34%, 97%), Certainty: Moderate], and psychological flexibility [SMD = 0.50 (0.35, 0.66), P <.001, I2 = 36% (0%, 83%), Certainty: Moderate] compared with controls at post-test. However, there was no significant positive effect on automatic thoughts [SMD = − 0.28 (− 0.69, 0.12), P =.17, I2 = 65% (0%, 97%), Certainty: Very low]. Notably, the positive effects of ACT on depression, anxiety and psychological flexibility were maintained at follow-up. Furthermore, the difference in acceptability between ACT and the control condition was not statistically significant (P ≥.05). Subgroup analyses indicated that face-to-face ACT was more effective than internet-based ACT. Conclusion According to the GRADE assessment, the certainty of the evidence ranges from very low to moderate. ACT appears to significantly improve depressive symptoms, anxiety, and psychological flexibility in individuals with depression. However, its effects on automatic thoughts and its acceptability still require further investigation. Meta-analysis registration on prospero : CRD42024533794.